Thoughts on landscape architecture - Jakob, Michael (4D Journal of Landscape Architecture and Garden Art, 2019)
When dealing with landscape architecture, we have to face a main problem, that is, a lack in theoretical founding. However, landscape architecture has known an extraordinary recent development; for the first time, for some major projects, the landscape architect has the lead, with the consequence of a higher visibility of the profession altogether.